Postoperative Changes of the Frontal Facial Soft Tissues in Patients with Mandibular Prognathism and Mandibular Deviation - MORITA, SHUICHI; YAMAKI, MASAKI; SAITO, ISAO; TAKEMURA, FUMI; SAITO, CHIKARA; TAKAGI, RITSUO (The Japanese Journal of Jaw Deformities, 2007)
This study was designed to evaluate the morphological changes of the frontal facial soft tissue in prognathic patients with mandibular deviation who had undergone One-jaw or Two-jaw surgery. The subjects were divided into two groups: Group 1 (Two-jaw group) consisted of 18 skeletal Class M female patients who had undergone Le Fort I osteotomy and Sagittal Splitting Ramus Osteotomy (SSRO). Group 2 (One-jaw group) comprised 18 skeletal Class HI female patients treated by only SSRO. A pair of pre-and post-operative standardized frontal facial photos were used for soft tissue analysis. The angular and linear measurements of the nose, lip, and lower facial lines were studied on the standardized frontal facial photos. The results obtained were as follows: 1. The quantity of postoperative Me deviation significantly decreased in the Two-jaw surgery group. 2. No change in the nose width was observed in the One-jaw surgery group, while the nose width was significantly increased after surgery in the Two-jaw surgery group. Asymmetric nose width before surgery changed to the symmetric one after surgery in the Two-jaw surgery group. 3. Lip width was significantly increased in the Twojaw group after surgery. The difference in the lip width between deviated and non-deviation sides was decreased in both groups after surgery. Asymmetric lip width before surgery improved in both groups after surgery. 4. The lip line and the lower facial line improved to a more suitable inclination after surgery in both groups.